2021
DOI: 10.3390/healthcare9121697
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices towards Diabetic Retinopathy among Primary Care Physicians of Saudi Arabia: A Multicenter Cross-Sectional Study

Abstract: Primary care physicians play a vital role in preventing the progression of diabetic retinopathy (DR) from the initial stages to the late stages. This questionnaire-based analytical cross-sectional study was carried out to assess the knowledge, attitude, practices, and their correlation among 274 randomly selected primary care physicians in Saudi Arabia. Among the studied population, high knowledge, attitudes, and practice scores were observed in 21.5%, 15%, and 29.2% of the physicians, respectively. The mean k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Our categorization is in accordance with the original Bloom’s cut-off point for assessing KAP and is supported by previous studies conducted among healthcare workers in the KSA and other parts of the world ( Mohammed Basheeruddin Asdaq et al, 2021 ; Feleke, Wale & Yirsaw, 2021 ; Abalkhail et al, 2021 ). Additionally, we combined low and medium scores as a single category for further analysis, and previous studies among the HCWs strongly support our categorization ( Abalkhail et al, 2021 ; Thirunavukkarasu et al, 2021 ; Ukwenya et al, 2021 ). The association of the subscales’ categories and sociodemographic characteristics was assessed by Pearson’s chi-square test.…”
Section: Discussionmentioning
confidence: 80%
“…Our categorization is in accordance with the original Bloom’s cut-off point for assessing KAP and is supported by previous studies conducted among healthcare workers in the KSA and other parts of the world ( Mohammed Basheeruddin Asdaq et al, 2021 ; Feleke, Wale & Yirsaw, 2021 ; Abalkhail et al, 2021 ). Additionally, we combined low and medium scores as a single category for further analysis, and previous studies among the HCWs strongly support our categorization ( Abalkhail et al, 2021 ; Thirunavukkarasu et al, 2021 ; Ukwenya et al, 2021 ). The association of the subscales’ categories and sociodemographic characteristics was assessed by Pearson’s chi-square test.…”
Section: Discussionmentioning
confidence: 80%
“…Our categorization is as per the original Bloom’s cut-off point and is supported by previous studies conducted among the HCWs in the KSA and other parts of the world. In Saudi Arabia, the HCWs are expected to have high knowledge (≥80%) of common public health problems, as they play a crucial role in preventing diseases by health education and delivering healthcare services implemented by the concerned authorities [ 19 , 20 ]. Hence, we combined low and good scores as a single category for logistic regression analysis, and previously conducted surveys among the HCWs strongly support and justify our categorization.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, this study has found that those with education related to medical field have higher knowledge ( β = 1.997; p < 0.01), higher positive attitudes ( β = 1.005; p < 0.01) and good practices ( β = 0.303; p < 0.05) related to diabetes. The higher KAP score is likely a result of higher exposure to comprehensive diabetes information which, in turn, contributes to a more positive attitude ( 49 ). Self-care education is crucial for effective diabetes management as it helps correct misconceptions regarding diabetes treatment and management ( 37 ).…”
Section: Discussionmentioning
confidence: 99%